The Investigation of Flory-Huggins Interaction Parameters for Amorphous Solid Dispersion Across the Entire Temperature and Composition Range - Yiwei Tian; Kaijie Qian; Esther Jacobs; Esther Amstad; David S. Jones; Lorenzo Stella; Gavin P. Andrews (MDPI AG, 2019)
Amorphous solid dispersion (ASD) is one of the most promising enabling formulations featuring significant water solubility and bioavailability enhancements for biopharmaceutical classification system (BCS) class II and IV drugs. An accurate thermodynamic understanding of the ASD should be established for the ease of development of stable formulation with desired product performances. In this study, we report a first experimental approach combined with classic Flory−Huggins (F−H) modelling to understand the performances of ASD across the entire temperature and drug composition range. At low temperature and drug loading, water (moisture) was induced into the system to increase the mobility and accelerate the amorphous drug-amorphous polymer phase separation (AAPS). The binodal line indicating the boundary between one phase and AAPS of felodipine, PVPK15 and water ternary system was successfully measured, and the corresponding F−H interaction parameters (χ) for FD-PVPK15 binary system were derived. By combining dissolution/melting depression with AAPS approach, the relationship between temperature and drug loading with χ (Φ, T) for FD-PVPK15 system was modelled across the entire range as χ = 1.72 − 852/T + 5.17·Φ − 7.85·Φ2. This empirical equation can provide better understanding and prediction for the miscibility and stability of drug-polymer ASD at all conditions.